Vascular Endothelial Growth Factor Induction of Muscle-Derived Stem Cells Enhances Vascular Phenotype While Preserving Myogenic Potential. Issue 4 (October 2017) - Wang, Howard D.; Guo, Qiongyu; Quan, Amy; Lopez, Joseph; Alonso-Escalante, Jose C.; Lough, Denver M.; Lee, WP Andrew; Brandacher, Gerald; Kumar, Anand R.
Abstract : Background: Previous work by our group and other laboratories have revealed that muscle-derived stem cells (MDSCs) may contain both myogenic and endothelial progenitors, making MDSCs a promising option for skeletal muscle regeneration. The purpose of this study was to investigate the impact of vascular endothelial growth factor (VEGF) induction on the vascular and myogenic potential of MDSCs. Methods: Muscle-derived stem cells were isolated from 4- to 8-week-old C57BL/6J mice using a preplate technique and recombinant human VEGFa was used as the induction agent. Cellular proliferation and migration were assessed using serial imaging and wound healing assays, respectively. Myosin heavy chain staining was performed to assess MDSC myotube formation. Vascular potential of MDSCs was measured by expression of CD31 and in vitro capillary tube formation. Results: Vascular endothelial growth factor stimulation led to a dose-dependent increase in MDSC proliferation ( P < 0.05) and migration kinetics ( P < 0.01). Control MDSCs had low levels of baseline expression of CD31, which was significantly upregulated by VEGF stimulation. Similarly, MDSCs demonstrated a basal capability for capillary tube formation, which was significantly increased after VEGF induction as evidenced by increased branches (5.91 ± 0.58 vs 9.23 ± 0.67, P < 0.01) and total tube length (11.73 ± 0.97 vs 18.62 ± 1.57 mm, P < 0.01). Additionally, the myogenic potential of MDSCs as measured by fusion index remained unchanged with increasing concentration of VEGF up to 250 ng/mL ( P = 0.77). Conclusions: Vascular endothelial growth factor induction enhances MDSC proliferation, migration, and endothelial phenotypes without negatively impacting myogenic potential. These results suggest that VEGF stimulation may improve vascularization of MDSC-based strategies for skeletal muscle regeneration.